Antiectoparasitic activity of the gum resin, gum haggar, from the East African plant, Commiphora holtziana - Birkett, Michael A.; Al Abassi, Sate; Kroeber, Thomas; Chamberlain, Keith; Hooper, Antony M.; Guerin, Patrick; Pettersson, Jan; Pickett, John A.; Slade, Robin; Wadhams, Lester J. (My University, 2008)
The mechanism of ixodid tick (Acari: Ixodidae) repellency by gum haggar, a resin produced by Commiphora holtziana (Burseraceae), was investigated by evaluating activity against the cattle tick, Boophilus microplus. In an arena bioassay, a hexane extract of the resin of C. holtziana exhibited a repellent effect lasting up to 5 h. The hydrocarbon fraction of the resin extract was shown to account for the repellent activity, and was analysed by coupled gas chromatography–mass spectrometry (GC–MS). Major sesquiterpene hydrocarbons were tentatively identified as germacrene-D, δ-elemene and β-bourbonene. The identity and stereochemistry of the former compound was confirmed as the (+)-isomer by peak enhancement using enantioselective GC, whereas the latter 2 compounds, which are most likely degradation products of germacrene-type precursors, were identified through isolation by preparative gas chromatography followed by microprobe-NMR spectroscopy. GC comparison of gum haggar with another resin, C. myrrha, which was inactive in the tick bioassay, showed that the latter contained much lower levels of these hydrocarbons. To assess the suitability of the gum haggar resin as a general acarine repellent, further tests were made on a major acarine pest of European and US animal husbandry systems, the red poultry mite, Dermanyssus gallinae (Acari: Dermanyssidae). Gum haggar extract, and the isolated hydrocarbon fraction, showed strong repellent effects in an olfactometer assay, and again gum myrrh showed no effect. These findings provide a scientific basis for the observed anti-tick properties of gum haggar, and demonstrate the potential for its development as a general acarine repellent for use in animal husbandry systems.
Keywords: Gum haggar; Commiphora holtziana; Repellent; Tick; Mite; (+)-Germacrene-D